2021
DOI: 10.1021/acs.cgd.1c00349
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interaction of Steps and Nanoislands during Growth of a Multicomponent Crystal

Abstract: Processes of formation of islands of individual components on terraces during step-flow growth of a multicomponent crystal are considered. This phenomenon is observed repeatedly in experiments and is possible when an excess of one of the components accumulates on the surface. In this case, multicomponent steps can be used as an additional tool to control the ensemble of islands on the crystal surface because, unlike single-component systems, it is possible to independently control the motion of the steps and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Let us use the conditions of the experiment, 62 at which the MBE growth of GaN was performed at a temperature of 730 °C. The equilibrium concentration of the gallium adatoms at the surface thus can be estimated 33 as n 0 aGa = 4 × 10 7 at cm −2 , the lifetime of the adatoms 63 equals τ aGa ∼ 10 −7 s, and their diffusion coefficient is D Ga ∼ 2 × 10 −8 m 2 s −1 . The diffusion length due to evaporation can then be estimated as .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Let us use the conditions of the experiment, 62 at which the MBE growth of GaN was performed at a temperature of 730 °C. The equilibrium concentration of the gallium adatoms at the surface thus can be estimated 33 as n 0 aGa = 4 × 10 7 at cm −2 , the lifetime of the adatoms 63 equals τ aGa ∼ 10 −7 s, and their diffusion coefficient is D Ga ∼ 2 × 10 −8 m 2 s −1 . The diffusion length due to evaporation can then be estimated as .…”
Section: Discussionmentioning
confidence: 99%
“…We should know the equilibrium surface concentrations of Ga adatoms n 0 aGa and vacancies n 0 vGa and their lifetimes. Let us use the conditions of the experiment, 62 at which the MBE growth of GaN was performed at a temperature of 730 C. The equilibrium concentration of the gallium adatoms at the surface thus can be estimated 33 as n 0 aGa ¼ 4 Â 10 7 at cm À2 , the lifetime of the adatoms 63 equals s aGa $ 10 À7 s, and their diffusion coefficient is D Ga $ 2 Â 10 À8 m 2 s À1 . The diffusion length due to evaporation can then be estimated as l e Ga ¼ ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi D Ga s aGa p $ 45 nm.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…In (Redkov and Kukushkin, 2020), the authors demonstrated that nucleation of islands consisting of pure components on the terraces between the steps is possible during step-flow growth, similar to the process of dew formation (refer to Figure 2A). In a subsequent study (Redkov and Kukushkin, 2021), it was shown that the precipitation of such islands can significantly impact the growth process, resulting in the formation of undesirable defects and inclusions in the crystal, and even cause different types of morphological instability (Bales and Zangwill, 1990). This phenomenon may occur when the surface concentration n ai (x) of a particular component on the surface between the steps exceeds the equilibrium single-component concentration n 0 ai (x) required for nucleation.…”
Section: Nucleation Of Pure Components On the Crystal Surfacementioning
confidence: 99%
“…Since the process of growth of an ordinary crystal and a pore are similar, similarly to the effect of advacancies on the growth of a crystal, adatoms on the surface of a pore can affect the rate of its vacancy growth. This work is a continuation of a series of works devoted to the growth and evolution of crystals [11][12][13][25][26][27][28] and pores in single-and multicomponent systems due to various mechanisms, and its main goal is to analyze the effect of adatoms on the pore surface on its vacancy growth of the pore according to the Barton-Cabrera-Frank mechanism, and find an expression for the dependence of the pore growth rate on the applied mechanical load and the properties of the crystal.…”
Section: Introductionmentioning
confidence: 99%